Penerapan teknologi irradiasi dalam proses pengolahan pangan - Rusliman, David; Suraduhita Prayitno, Tantra (Jurnal Inovasi Pangan dan Gizi, 2024)
Background: The development of nonthermal technology increases with the times. This technology includes the application of food irradiation which includes the electron beam method, X-rays, and gamma irradiation. Methods: The electron beam method is a technique for preserving food using high-energy electron beams, while the x-ray method is a technique that uses high-energy X-rays to preserve food. Findings: X-rays are produced by shooting a high-energy electron beam at a metal target, producing X-ray radiation which is then used to irradiate food. The gamma irradiation method is a technique that uses gamma radiation, usually from radioactive sources such as Cobalt-60 or Cesium-137, to preserve food. The gamma irradiation method is one of the potential nonthermal methods to be applied to strawberry fruit products with a maximum dose of 2 kGy and can extend the shelf life of strawberries up to 12 days and maintain the nutrients contained therein by adding storage at a temperature of 4 ° C, in addition, edible film applications can be used to help the packaging process so as to maintain the quality of strawberry fruit products. Conclusion: The explanation of several nonthermal methods that can be applied to extend the shelf life of strawberry products. Novelty/Originality of this article: reference for nonthermal food processing is the novelty of this article review.